Sulfonated poly(arylene ether) membranes with high rejection of monovalent salts even in the presence of mixed salt feeds containing multivalent salts

By using sulfated polyarylene ethanol polymers as membrane materials, the problem that existing water-degrading membranes are difficult to remove monovalent anions when multivalent cations exist, achieving efficient and permeable water degradation effect.

JP7670268B2Active Publication Date: 2025-04-30BOARD OF RGT THE UNIV OF TEXAS SYST +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2020543106
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-02-09
Filing Date
2019-02-09
Publication Date
2025-04-30
Estimated Expiration
2039-02-09

AI Technical Summary

Technical Problem

When the existing water degradation membranes are present, it is difficult to effectively remove monovalent anions, and they do not have good removal performance for water sources with multivalent cations.

Method used

Sulfonated poly(arylene ether)-like polymers are used as membrane materials, and a film with high water permeability and good polyvalent cation exclusion properties are formed by chemical reaction or post-sulfation treatment.

Benefits of technology

When the multivalent cation is present, it can efficiently remove monovalent anions in water, significantly improve the removal performance of the water degradation membrane, and maintain permeability to water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670268000093
    Figure 0007670268000093
  • Figure 0007670268000094
    Figure 0007670268000094
  • Figure 0007670268000095
    Figure 0007670268000095
Patent Text Reader

Abstract

Described herein are water desalination membranes and methods for desalination. Sulfonated poly(arylene ether) polymers are also disclosed, including those containing one or more sulfonate groups at various points along the polymer chain. The polymers can be used as at least a portion of a water desalination membrane. The polymers described herein can be used to inhibit the release of water-soluble ionic species (e.g., Na ions) across membranes made from the polymers while allowing water to pass through. + and Cl - Chlorine-stable polymers and polymers that exhibit good performance for excluding monovalent cations in the presence of multivalent cations are described.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of and priority to U.S. Provisional Application Nos. 62 / 628,347 and 62 / 628,349, both filed February 9, 2018. These applications are hereby incorporated by reference in their entireties. [Background technology]

[0002] Clean water is important for the safety, protection and survivability of humankind. Nearly 41% of the Earth's population lives in hydro-stressed regions, and water scarcity will be exacerbated by population growth. According to the United States Geological Survey, about 96.5% of the Earth's water is located in the oceans, with the remainder in surface and groundwater, mostly frozen in glaciers and ice caps. Approximately 96% of the total water is in salt solutions, and only about 0.8% is considered available fresh water. Thus, desalination of saltwater is important to address the problem of water scarcity. High-temperature thermal desalination methods are not energy efficient because they rely on energy-intensive phase changes and require large amounts of fuel to evaporate the water. Membrane-based desalination methods are more economical and energy efficient than high-temperature methods for seawater desalination and other related water purification applications. Anionic sulfonated poly(arylene ether) membranes for water desalination have been shown to have high water permeability and good rejection of monovalent salts (e.g., NaCl), but conventional membranes made from such materials typically have poor rejection of multivalent cations (e.g., Ca). 2+ , Mg 2+ In the presence of monovalent ions (e.g., Na + Cl - ), further development is needed, given that multivalent salts are found in almost all sources of saline and surface waters. Summary of the Invention

[0003] The present invention relates generally to methods and systems for desalination of water, and compositions useful in desalination of water. More particularly, embodiments of the present invention provide sulfonated poly(arylene ether) polymers, methods for making such polymers, and methods and systems for using such polymers in desalination of water.

[0004] In one embodiment, linear sulfonated poly(arylene ether)s are provided. The linear sulfonated polymers may be copolymers, such as polymers containing two or more different monomer units. The polymers may be polymerized via a chemical reaction between the monomers. The linear sulfonated copolymers of this embodiment may be formed from a presulfonated monomer, where one or more of the substituents of the monomer contain a sulfonate group (e.g., -SO3 - , SO3Na, SO3K, etc. In some cases, a pre-sulfonated monomer and a non-sulfonated monomer are polymerized to form a copolymer. In other cases, a non-sulfonated monomer is polymerized to form a copolymer and then the sulfonate group is added in a post-sulfonation reaction.

[0005] In a specific embodiment, the copolymer has the structure [ka] wherein each L 1 is independent [ka] and each L 2 is independent [ka] and each L 3 are independently single bonds, [ka] and one Y 1 is SO3Z and another Y 1is H, Z is a counterion (e.g., a metal ion), and each R is independently H, F, or CH. The value for x can be 0 to 1, and the value for n can be any suitable number for the polymer, such as, for example, 2 to 100,000.

[0006] In another specific embodiment, the copolymer has the structure [ka] wherein each L 1 is independent [ka] and each L 2 is independent [ka] and each L 3 are independently single bonds, [ka] and Y 1 is SOZ or H, Z is a counterion (e.g., a metal ion), and each R is independently H, F, or CH. The value for x can be 0 to 1, and the value for n can be any suitable number for the polymer, such as, for example, 2 to 100,000.

[0007] In some embodiments, end groups at one or both ends of the polymer may be included, and molecular weight may be controlled by adjusting the stoichiometry between the monomers and terminating agents by conventional methods to synthesize step-extending copolymers. The end groups may include or comprise alkenyl groups, styrene groups, fluorinated styrene groups, carbonyl groups, carboxylic acid esters, amino groups, phenolic groups, or other crosslinkable groups, which may be useful to enable crosslinking between polymer chains, such as when exposed to a crosslinking agent. Optionally, the copolymer may include or further comprise one or more end groups A, each end group A being independently: [ka] The crosslinked network can be formed from any of the copolymers described herein by subjecting a copolymer or a blend of copolymers of different molecular weights containing one or more crosslinkable groups to a crosslinking agent such as heat, light, a free radical initiator, an epoxy reagent, etc. Also, low molecular weight crosslinkable monomers can be added to these copolymers to form crosslinked networks from such mixtures.

[0008] Exemplary crosslinkable oligomeric macromonomers according to this embodiment can have the following structure: [ka] In the formula, each L 1 is independent [ka] and each L 2 is independent [ka] and each L 3 are independently single bonds, [ka] and Y 1 is H or SO3Z, where Z is a counter ion (e.g., Na + Or K + and each R is independently H, F, or CH3; and each A is independently [ka] It is.

[0009] Another crosslinkable oligomeric macromonomer prepared by post-sulfonation can have the following structure: [ka] In the formula, each L 1 is independent [ka] and each L 2 is independent [ka] and each L 3 are independently single bonds, [ka] and each Y 1 are independently H or SOZ, where Z is a counter ion (e.g., Na + Or K + each R is independently H, F, or CH3, and each A is independently [ka] where Y 1 is SO3Z or H, [ka] It is.

[0010] The functional oligomeric macromonomers of the previous embodiment can optionally be crosslinked, such as after exposure to a crosslinking agent. Optionally, blends of functional oligomeric macromonomers with crosslinkable end groups or of different molecular weights can be crosslinked together, or lower molecular weight monomers or crosslinking agents can be added to the mixture.

[0011] The copolymers described herein can have any suitable molecular weight or length. The copolymers described herein are generally random copolymers having a fractional amount (x or 1-x) of sulfonate-containing structural units ranging from about 5% to about 95%, sometimes referred to herein as the degree of sulfonation. Exemplary fractional amounts of sulfonate-containing structural units include 5% to 10%, 10% to 15%, 15% to 20%, 20% to 25%, 25% to 30%, 30% to 35%, 35% to 40%, 40% to 45%, 45% to 50%, 50% to 55%, 55% to 60%, 60% to 65%, 65% to 70%, 70% to 75%, 75% to 80%, 80% to 85%, 85% to 90%, or 90% to 95%. Copolymer molecular weight or length and / or fractional amount of sulfonate-containing structural units in the copolymer can result in the required properties of the copolymer, which in turn can affect the suitability of the polymer for use in different applications. For example, the amount of sulfonation can be correlated with the ion exchange capacity (IEC) of the copolymer. In some cases, IEC can be expressed in units of milliequivalents per gram of dry polymer. Exemplary IEC values ​​for the copolymers described herein can range from about 0.1 to about 5, such as 0.1 to 0.5, 0.5 to 1, 1 to 2, 2 to 3, 3 to 4, or 4 to 5.

[0012] In another aspect, synthetic methods are described herein. In some embodiments, methods of producing copolymers are described. An exemplary method of producing a copolymer includes: [ka] of [ka] and optionally with an aminophenol to end-capping the copolymer and control molecular weight, to produce the copolymer, wherein each L 1 is independent [ka] And L 2 teeth, [ka] And L 3 is a single bond, [ka] wherein each R is independently H, F, or CH3, and X is a halogen. Optionally, the method of this embodiment further comprises exposing the copolymer terminated with a phenol or with an aromatic amine obtained from reaction with an aminophenol to a crosslinking agent. Optionally, the method of this embodiment further comprises exposing the copolymer having phenol end groups to a crosslinking agent. [ka] or reacting the copolymer with a phenol or aminophenol end group containing an acryloyl halide (e.g., acryloyl chloride), a methacryloyl halide (e.g., methacryloyl chloride), an isocyanatoethyl acrylate, or an isocyanatoethyl methacrylate to produce an end-functionalized copolymer. Optionally, the end-functionalized copolymer can be crosslinked by exposure to heat, light, a free radical initiator, or a crosslinking agent such as an epoxy reagent.

[0013] Another method for producing the copolymer is [ka] of [ka] and optionally together with an aminophenol to form a copolymer, wherein each L 1 is independent [ka] And L 2 teeth, [ka] And L 3 is a single bond, [ka] where each R is independently H, F, or CH3, and X is a halogen. The stoichiometry can be offset to produce a controlled molecular weight macromonomer containing phenol end groups by prior art methods for step extension polymers, or aminophenol can be added in calculated amounts to produce a controlled molecular weight copolymer containing aromatic amine end groups. The phenol or aromatic amine terminated macromonomer is then post-sulfonated to produce L 2 In one embodiment, the method can produce approximately one SOZ group in each ring of the formula: where Z is a counterion. Optionally, the method can produce a phenol-terminated or sulfonated copolymer. [ka] or reacting the phenol- or aminophenol-terminated or sulfonated copolymer with an acryloyl halide, a methacryloyl halide, an isocyanatoethyl acrylate, or an isocyanatoethyl methacrylate to purify the end-functionalized or end-functionalized sulfonated copolymer. Optionally, the method of this aspect further comprises reacting the end-functionalized copolymer with a sulfonating reagent, such as sulfuric acid, to post-sulfonate the end-functionalized copolymer to produce an end-functionalized sulfonated copolymer. Optionally, the method of this aspect can include a crosslinking step, such as a step including via a crosslinking reaction by subjecting the end-functionalized phenol, aromatic amine derived from aminophenol, fluorostyrene, fluorinated aromatic compound, acrylate, acrylamide, methacrylate, methacrylamide, or urea or urethane acrylate or urethane methacrylate-terminated copolymer to a crosslinking agent, such as heat, light, a free radical initiator, or an epoxy reagent.

[0014] It will be appreciated that each of the above groups or structures in this Summary section can be unsubstituted or substituted, meaning that any hydrogen atom can be replaced by another group as described below.

[0015] In another aspect, a water desalination membrane is described. An exemplary desalination membrane can include any one or more of the copolymers described herein. A variety of different properties can be established in the desalination membrane by the selection of the appropriate copolymer. For example, it may be desirable to employ copolymers containing crosslinkable end groups to allow crosslinking in the membrane, such as to provide or increase mechanical robustness in the membrane. Linear sulfonated poly(arylene ether sulfones) are known to be relatively stable to aqueous solutions of chlorine compounds that are commonly used as disinfectants in water treatment systems. To maintain chlorine stability in the crosslinked network, it may be desirable to employ copolymers containing end groups or crosslinkers that are also stable to chlorine, such as fluorinated end groups for crosslinking. Advantageously, membranes including the polymers and copolymers described herein can be crosslinked with mixed valence salts (e.g., Na + and K + with an appropriate counterion, as well as monovalent salts such as Ca 2+ , Mg 2+ The membranes may be useful for desalinating waters containing multivalent salts, such as salts containing , with appropriate counterions, as well as other ionic species. While conventional sulfonated desalination membranes can exhibit poor performance in rejecting monovalent ions when divalent cations are present in the feed, membranes containing the polymers and copolymers described herein exhibit high rejection of monovalent ions despite the presence of divalent or multivalent cations in the feed. For example, the water desalination membranes described herein can exhibit greater than 90% rejection of water-soluble monovalent ions in the presence of multivalent cations. In some cases, the rejection can be about 90% or more, about 91% or more, about 92% or more, about 93% or more, about 94% or more, about 95% or more, about 96% or more, about 97% or more, about 98% or more, about 99% or more, about 99.5% or more, or about 99.9%.

[0016] In another aspect, also described herein are methods for desalinating water utilizing the sulfonated poly(arylene ether) membranes of the present invention, including using water containing mixed salts, and combinations of salts with mixed valences.

[0017] The method of this embodiment includes exposing a first side of a sulfonated poly(arylene ether) water desalination membrane to a saltwater solution, the saltwater solution including a mixture of monovalent ions and polyvalent cations, the water desalination membrane being capable of rejecting at least 90% of the monovalent salts even in the presence of polyvalent salts, and pressurizing the saltwater solution to drive a reverse osmosis process, where water from the saltwater solution passes from the first side of the water desalination membrane to a second side of the water desalination membrane, and where at least 90% of the monovalent ions are rejected from passing through the water desalination membrane in the presence of the polyvalent cations. Optionally, the concentration of the polyvalent cations is between 1 parts per million and 5,000 parts per million. For example, the concentration of the polyvalent cations may be at least or about 100 parts per million, at least or about 500 parts per million, at least or about 1000 parts per million, at least or about 1500 parts per million, or at least or about 2000 parts per million. In some cases, the concentration of the monovalent cations is 500 parts per million to 50,000 parts per million. For example, the concentration of the monovalent ions may be at least or about 1000 parts per million, at least or about 5000 parts per million, at least or about 10,000 parts per million, at least or about 15,000 parts per million, or at least or about 20,000 parts per million. In some cases, the water is saline water or seawater.

[0018] As noted above, the polymers and copolymers described herein can be stable in the presence of chlorine and chlorine compounds due to the excellent stability of the sulfonated and non-sulfonated poly(arylene ether) compounds. Optionally, the saltwater solution includes a halide-based sterilant, and the water desalination membrane remains substantially unoxidized by the halide-based sterilant.

[0019] These and other embodiments of the present invention, along with many of the advantages and features of the present invention, will be described in more detail in conjunction with the following text and accompanying drawings. [Brief description of the drawings]

[0020] [Figure 1] Exemplary synthetic routes for polymer synthesis are provided.

[0021] [Diagram 2] An overview of the post-sulfonation of polymers is provided.

[0022] [Diagram 3] 1 provides a schematic diagram of a water desalination process.

[0023] [Figure 4] An example of a typical desalination membrane structure prepared by interfacial polymerization of m-phenylenediamine and trimesoyl chloride is provided.

[0024] [Diagram 5] We provide data showing the surface roughness of polymer membranes. Top: interfacially polymerized polyamide membrane, bottom: sulfonated polysulfone membrane.

[0025] [Figure 6] 1 provides a schematic diagram of an electrodialysis system.

[0026] [Figure 7] An overview of exemplary cross-linking reactions for forming ion exchange membranes is provided.

[0027] [Figure 8] Provides an overview of exemplary crosslinking reactions for forming sulfonated poly(arylene ether) networks. (The 5k or 10k blocks refer to sulfonated poly(arylene ether) macromonomers.)

[0028] [Figure 9] Provides data showing salt rejection and water permeability of different membranes. The top structure is BPS-XX and the bottom structure is BisA-XX. XX refers to the unit of disulfonation degree.

[0029] [Figure 10]Data showing salt rejection and water permeability of different membranes are provided. One line refers to data for a linear copolymer having the above structure shown in Figure 9. The other line refers to data for a similar structure in which an oligomer with a molecular weight of 10,000 g / mol is crosslinked with a tetrafunctional epoxy reagent (TGBAM).

[0030] [Figure 11] Salt permeability in membrane samples <ps>1 provides a photograph of an exemplary penetrant test cell for evaluating

[0031] [Figure 12] The relationship between salt permeability and water uptake for different membranes is shown. The membranes are epoxy crosslinked networks where the precursor oligomer molecular weight was 5000 g / mol (mBX-5) or 10,000 g / mol (mBX-10). X refers to the percentage of repeating units that were sulfonated x 10-1. The oligomers were prepared from premonosulfonated dihalogenated monomers reacted with dichlorodiphenylsulfone and biphenol. [Figure 13] Salt permeability versus fixed charge concentration is shown. The membranes are epoxy crosslinked networks where the precursor oligomer molecular weight was 5000 g / mol (mBX-5) or 10,000 g / mol (mBX-10). X refers to the percentage of repeating units that were sulfonated x 10-1. The oligomers were prepared from premonosulfonated dihalogenated monomers reacted with dichlorodiphenylsulfone and biphenol.

[0032] [Figure 14] Data showing sodium ion passage as a function of calcium ion feed concentration for different membranes is provided. Table 2 below, and the subsequent constructions, can be used with respect to these figures. [ka] [Figure 15] Data showing sodium ion passage as a function of calcium ion feed concentration for different membranes is provided. Table 2 below, and the subsequent constructions, can be used with respect to these figures. [ka]

[0033] [Figure 16] Exemplary synthetic routes for polymer synthesis are provided.

[0034] [Figure 17] Provides polymer structure data by NMR. [Figure 18] Provides polymer structure data by NMR. [Figure 19] Provides polymer structure data by NMR.

[0035] [Figure 20] A light scattering detector is used to provide size exclusion chromatography results that characterize the molecular weight and molecular weight distribution for different polymers. (The x-axis refers to time in minutes and y is the degree of light scattering intensity.)

[0036] [Figure 21A] FIG. 21C shows hydrated mechanical properties as a function of water uptake for crosslinked, post-sulfonated membranes containing hydroquinone. [Figure 21B] FIG. 21C shows hydrated mechanical properties as a function of water uptake for crosslinked, post-sulfonated membranes containing hydroquinone.

[0037] [Figure 22A] FIG. 21C provides hydration stress / strain data for membranes of the crosslinked copolymer described in FIG. [Figure 22B] FIG. 21C provides hydration stress / strain data for membranes of the crosslinked copolymer described in FIG.

[0038] [Figure 23] FIG. 21C provides salt permeability data for the crosslinked membrane illustrated. [Figure 24] FIG. 21C provides salt permeability data for the crosslinked membrane illustrated.

[0039] [Diagram 25] Exemplary synthetic routes for polymer synthesis are provided.

[0040] [Figure 26] Exemplary post-sulfonation reactions of oligomeric macromonomers are provided.

[0041] [Figure 27] 1 provides a general overview of fluorine derivatization.

[0042] [Figure 28A] NMR data for the unreacted and reacted fluoro-derivatives of the polymer illustrated in FIG. 21C are provided. [Figure 28B] NMR data for the unreacted and reacted fluoro-derivatives of the polymer illustrated in FIG. 21C are provided.

[0043] [Figure 29] 21C, which provides data showing the percent sulfonation at different temperatures for a polymer having the structure shown in FIG. 21C, in which 29% of the units contain hydroquinone.

[0044] [Diagram 30] 21C provides differential refractive index data for the polymers illustrated in FIG.

[0045] [Diagram 31] A light scattering detector is used to provide size exclusion chromatography results characterizing the molecular weight and molecular weight distribution for the oligomeric macromonomers as illustrated in FIG. 21C both before and after sulfonation.

[0046] [Diagram 32] An example of epoxy crosslinking of a post-sulfonated aminophenol terminated oligomeric macromonomer as illustrated in FIG. 21C is provided.

[0047] [Diagram 33] 33 provides ion exchange capacity data for epoxy crosslinked membranes as illustrated in FIG. 32. [Diagram 34] 33 provides ion exchange capacity data for epoxy crosslinked membranes as illustrated in FIG. 32.

[0048] [Diagram 35] 33 provides data on hydrated mechanical properties as a function of water uptake for linear and epoxy crosslinked oligomers as illustrated in FIG. 32. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0049] The present invention relates to a water desalination membrane and a method for desalinating water. The water desalination membrane may employ a poly(arylene ether) that may include one or more sulfonate groups at various points along the polymer chain, either directly attached to the chain or pendant to the polymer chain. In some embodiments, the polymer may be produced from a sulfonated monomer, and the resulting sulfonated polymer may be referred to herein as a pre-sulfonated polymer. In some embodiments, the polymer may be produced from a non-sulfonated monomer, but is subjected to a post-polymerization sulfonation treatment, such as by exposing the polymer to sulfuric acid, and the resulting sulfonated polymer may be referred to herein as a post-sulfonated polymer. The sulfonated polymers described herein are useful for preventing the transport of water-soluble ionic species (e.g., NaCl) across membranes made from the polymers while allowing water to pass through.

[0050] The sulfonated polymers described herein offer numerous advantages. For example, the sulfonated polymers described herein exhibit good performance for rejecting monovalent ions in the presence of multivalent cations. This contrasts with data on the separation of salty feedwater by reverse osmosis for prior sulfonated poly(arylene ether) membranes. See, for example, A.E. Allegrezza, Jr., B.S. Parekh, P.L. Parise, E.J. Swiniarski, J.L. White, Chlorine resistant reverse osmosis modules, Desalination, 64 (1987), 285-304; P.L. Parise, A.E. Allegrezza, Jr., B.S. Parekh, Reverse Osmosis, Chlorine resistant reverse osmosis membrane and module, based on a paper presented at the first annual Ultrapure Water conference and exposition, Philadelphia, PA, April 13-15, 1987.; and Derek E. Stevens, Bill Mickols, Caleb V. Funk, Asymmetric reverse osmosis sulfonated poly(arylene ether sulfone) copolymer membranes, Journal of Membrane Science, 452 (2014), 193-202. This aspect can be important for practical use in water desalination, since multivalent cations are always or nearly always present in the source water feed used in desalination. Additionally, embodiments of the present invention provide polymers that are stable in chlorinated water. Although sulfonated poly(arylene ether)s have previously been shown to be resistant to degradation by aqueous chlorine compounds, this high chemical stability is an advantage over interfacial polyamide desalination membranes, which comprise most of the current desalination membrane market. Chlorine and chlorine compounds are commonly used in water treatment to sterilize water, but such sterilizing agents can degrade some polymer membranes.For desalination, a dechlorination process can be used to remove chlorine compounds from water for desalination using membranes. Advantageously, membranes made from the polymers described herein exhibit good stability in water containing chlorine disinfectant, which may allow for the elimination or reduction of the dechlorination effect prior to desalination.

[0051] The sulfonated polymers described herein can include monosulfonated polymers, which can refer to a single sulfonate group attached to one of the copolymer units or can refer to two sulfonate groups attached to one of the copolymer units. In some cases, each of these configurations can find practical utility in semipermeable membranes used in water desalination.

[0052] An exemplary copolymer has the following structure: [ka] wherein each L 1 is independent [ka] and each L 2 is independent [ka] and each L 3 are independently single bonds, [ka] where Z is a counterion (e.g., a metal ion) and each R is independently H, F, or CH3. The value for x can be 0 to 1, and the value for n can be any suitable number for the polymer, e.g., 2 to 100,000. In the case of a monosulfonated polymer, one Y 1 is SO3Z, and another Y 1 is H. In the case of disulfonated polymers, any Y 1 Also, the polymer can be SO3Z. These polymers can optionally be crosslinked, such as after exposure to a crosslinking agent.

[0053] Another exemplary copolymer, which may be monosulfonated or disulfonated, has the structure [ka] wherein each L 1 is independent [ka] and each L 2 is independent [ka] and each L 3 are independently single bonds, [ka] and each Y 1 is H or SO3Z, where Z is a counter ion (e.g., Na + Or K + each R is independently H, F, or CH3; each A is independently an aminophenol; [ka] wherein X is a halogen.

[0054] Another exemplary copolymer has the following structure: [ka] may include In the formula, each L 1 is independent [ka] and each L 2 is independent [ka] and each L 3 are independently single bonds, [ka] and Y 1 is SOZ or H, Z is a counterion, and each R is independently H, F, or CH. Such polymers can correspond, for example, to post-sulfonated copolymers.

[0055] Another exemplary copolymer that can correspond to the post-sulfonated copolymer has the structure [ka] wherein each L 1 is independent [ka] and each L 2 is independent [ka] and each L 3 are independently single bonds, [ka] and each Y 1 is SO3Z or H, where Z is a counter ion (e.g., Na + Or K + each R is independently H, F, or CH3; and each A is independently [ka] They are aromatic amines derived from phenols or aminophenols, where X is a halogen.

[0056] In the above exemplary copolymers, the value for x can be 0 to 1, and the value for n can be any suitable number for the polymer, such as, for example, 2 to 100,000. Any of the above groups can have one or more hydrogen atoms optionally replaced by another group. These polymers can optionally be crosslinked, such as after exposure to a crosslinking agent.

[0057] Generally, the terms and phrases used herein have their art-recognized meanings, which can be appreciated by reference to standard texts, journal references, and contexts known to those of skill in the art. The following definitions are provided to clarify their specific use in the context of the present invention.

[0058] "Linear polymer" is used to describe a polymer that exhibits an overall non-crosslinked configuration in its individual molecular form.

[0059] In one embodiment, the disclosed compositions or compounds are isolated or purified. In one embodiment, an isolated or purified compound is at least partially isolated or purified as understood in the art.

[0060] The molecules disclosed herein contain one or more ionizable groups. Ionizable groups include groups that can remove (e.g., -SO3H) or add (e.g., amines) protons, and groups that can tetramerize. All possible ionic forms of such molecules and their salts are intended to be included individually in the disclosure of this specification. It will be recognized that for salts of the compounds described herein, a wide variety of available counterions can be selected that are appropriate in the context of the present invention for a given application. In a specific application, the selection of anion or cation provided in the preparation of the salt can result in an increase or decrease in the solubility of the salt.

[0061] As used herein, the terms "group" and "moiety" can refer to the functional groups of a compound. A group of the disclosed compounds refers to an atom or collection of atoms that is part of the compound. A group of the disclosed compounds can be attached to other atoms of the compound through one or more covalent bonds. A group can also be characterized in terms of its valence state. The present disclosure includes groups characterized by valence states such as monovalent, divalent, trivalent, etc. In embodiments, the term "substituent" can be used interchangeably with the terms "group" and "moiety."

[0062] As is common and well known in the art, hydrogen atoms are not always explicitly shown in the chemical formulas disclosed herein, for example, hydrogen atoms bonded to carbon atoms of aliphatic, aromatic, alicyclic, carbocyclic and / or heterocyclic rings are not always explicitly shown in the recited formulas.For example, in the context of the description of any specific formulas and structures recited, the structures provided herein are intended to convey the chemical composition of the compounds disclosed in the methods and compositions.It will be recognized that the structures provided do not indicate the specific positions of the atoms and bond angles between atoms of these compounds.In the case of substituted groups, one or more hydrogen atoms can be replaced by any one or more of the other groups described herein.

[0063] The present invention can be further understood by the following non-limiting examples.

[0064] Sulfonated poly(arylene ether) membranes for water desalination can be prepared by direct polymerization with presulfonated monomers or by synthesizing nonsulfonated poly(arylene ether)s followed by sulfonation of the synthesized polymer, a process known as "postsulfonation" since the sulfonation step is performed after the polymer is synthesized. In the case of postsulfonation, the sulfonate groups can be added to linear copolymers, to end-functional macromonomers, or to crosslinked networks. First, presulfonated monomers can be used to synthesize poly(arylene ether sulfones) or poly(arylene ether ketones). This method has the advantage of allowing control over the degree of sulfonation by selecting the desired level of sulfonated comonomer. This method also produces randomly sulfonated copolymers. Moreover, there is no molecular weight reduction that can occur due to undesired reactants in the postsulfonation process. Sulfonated monomers with either chlorine or fluorine reactive groups produce such structures. Analogous sulfonated aromatic ketone monomers are also included. For the case of directly polymerized sulfonated poly(arylene ether ketone), 4,4'-difluorobenzophenone would be used to replace 4,4'-dichlorodiphenyl sulfone as illustrated in Figure 1, or sulfonated 4,4'-difluorobenzophenone can be incorporated.

[0065] Second, a non-sulfonated poly(arylene ether) can be synthesized and then selectively post-sulfonated only at those aromatic rings that are not deactivated to electrophilic aromatic substitution post-sulfonation, as shown in Figure 2. For such a method, the post-sulfonation conditions can be carefully optimized to sulfonate only those rings that are not deactivated (to electrophilic aromatic sulfonation) to avoid molecular weight degradation.

[0066] Membrane-based water desalination can be accomplished by reverse osmosis or by electrodialysis. In both processes, the separation membrane is nonporous and the separation process occurs by a solution dispersion mechanism. Reverse osmosis utilizes a saline solution feed water pressurized against the membrane, where the pressure must be at least sufficient to overcome the osmotic pressure (Figure 3). The membrane can be asymmetric or employ a thin film composite with sulfonated poly(arylene ether) on a porous polymer support. An effective reverse osmosis membrane must be able to select water fluxes with high salt rejection, and the separation layer must be thin (about 100-500 nm) to obtain sufficiently high water fluxes. Current polyamide membranes (Figure 4) degrade in the presence of conventional chlorination disinfectants, so water must be pretreated with chlorine and dechlorinated before passing through the membrane and then rechlorinated after desalination. Moreover, the nature of interfacial polymerization over the porous polymer supports used in conventional polyamide thin film composite membranes results in a rough surface for the sulfonated poly(arylene ether) membranes of the present invention (Figure 5). Rough surfaces are subject to fouling by salts and other impurities in the water during the desalination process. Fouling of interfacial polyamide thin film composites is a major obstacle to the desalination process.

[0067] Electrodialysis utilizes a stack of alternating anion exchange membranes (AEM) and cation exchange membranes (CEM) with a compartment between the membranes for the introduction of a saline feed water placed between the anode and cathode. An electric current is applied that drives anions from the feed water to the positive electrode and cations to the negative electrode (FIG. 6). The CEM is composed of a polyelectrolyte polymer with anions immobilized on its structure. The sulfonated poly(arylene ether) of the present invention can function as a CEM because it also has anions immobilized on its structure. The sulfonated poly(arylene ether) must selectively transport cations from the feed water through the membrane and must exclude co-anions (e.g., transport sodium ions and exclude chloride ions). Similarly, the AEM contains immobilized cations and the membrane of the AEM must selectively transport anions and exclude co-cations (e.g., transport chloride and exclude sodium ions). Selectivity is driven by electrostatic Donnan exclusion of the co-ions by the ion-immobilized membrane. Therefore, the concentration of ions immobilized on the membrane must be high. This means that the number of immobilized ions per gram of dry polymer must be high and the water absorption must remain relatively low. Ideally, the electrodialysis membrane should be as thin as possible to minimize electrical resistance, since as electrical resistance increases, more energy is required to perform the desalination process. Electrodialysis membranes can include cross-linked polyelectrolytes synthesized by free radical copolymerization. Common commercially available monomers include chloromethylstyrene-divinylbenzene, which can be post-aminated to produce AEM, sulfonated styrene-divinylbenzene to produce CEM, or alternative monomers as shown in Figure 7. Since the mechanical properties of commercially available AEM and CEM are poor, the properties must be reinforced with a significant amount of hydrophobic polymer used in the laminate for electrodialysis. This increases the electrical resistance area in the electrodialysis process, which requires additional energy to operate and reduces the effective membrane area, which increases capital costs.The sulfonated poly(arylene ether)s of the present invention have superior mechanical properties to conventional CEMs and therefore may not require as much hydrophobic polymer support.

[0068] Structure-Property Relationships for Linear and Crosslinked Disulfonated Poly(arylene ether sulfones) from Pre-disulfonated Sulfone Monomers. Linear, directly polymerized sulfonated poly(arylene ether sulfones) containing either biphenol or bisphenol A as the bisphenol monomer were produced with systematically varying degrees of sulfonation by utilizing pre-disulfonated monomers. In addition, the .about.5000 and .about.10,000 g / mol M n Controlled molecular weight oligomers of were prepared as bisphenol monomers, where biphenol or bisphenol A was terminated with m-aminophenol to give aromatic primary amine end groups. The oligomers were reacted with the multifunctional epoxy reagent tetraglycidylbis(aminophenyl)methane (TGBAM) to produce crosslinked membranes, as shown in Figure 8. The amount of sulfonate anion immobilized on these linear and crosslinked copolymers is expressed as ion exchange capacity (IEC) in milliequivalents per gram of dry polymer. For a given IEC, the amount of water that can be absorbed (water uptake) decreases with network formation (Table 1). [Table 1] Table 1. XLBx-y: XL=crosslinked type, Bx=degree of disulfonation, y=block length of precursor oligomer at 1000 blocks. BPS-XX=linear biphenol-based polysulfone with pre-disulfonated monomer and XX=degree of disulfonation. [ka] For example, the crosslinked entry number 4 in Table 1 (oligomer M of about 10,000 g / mol) n The linear BPS-50 (registry no. 8 in Table 1) with 50% disulfonated comonomer units and an IEC of 1.93 has a very high water uptake of 105%, while the crosslinked XLB60-10 (10,000 g / mole oligomer, 60% disulfonated) has an IEC of 2.03 and a water uptake of only 63%, whereas the linear BPS-50 (registry no. 8 in Table 1) with 50% disulfonated comonomer units and an IEC of 1.93 has a very high water uptake of 105%, while the crosslinked XLB60-10 (10,000 g / mole oligomer, 60% disulfonated) has an IEC of 2.03 and a water uptake of only 63%. It is therefore apparent that the amount of absorbed water is bound by network formation, and thus the concentration of immobilized ions (moles of ions / liter of water absorbed) is inherently higher in the networks than in analogous linear copolymers.

[0069] As the degree of disulfonation in the linear type material increases, the water permeability increases and the salt rejection decreases (Figure 9). This can be directly related to the amount of water absorbed. However, a comparison of the same properties of similar crosslinked materials clearly shows that as the water permeability increases, a better retention of high salt rejection is achieved for the crosslinked material versus the linear type membrane (Figure 10). Furthermore, this can be related to the relatively smaller amount of water absorption in the crosslinked network versus the linear material. For example, the water uptake of linear BPS-40, with 40% of the units disulfonated, is 55% and the IEC is 1.78, whereas the sodium chloride rejection of the crosslinked membranes with IECs of 1.6 (26.6% water uptake) and 1.85 (41.3% water uptake) is significantly better. The sodium chloride permeability was measured by monitoring the conductivity of the receptor solution as ions diffused through a series of crosslinked disulfonated poly(arylene ether sulfone) membranes. The diffusion cell is illustrated in Figure 11. 12 and 13 respectively show that water uptake decreases with decreasing salt passage and a corresponding desirable decrease in salt passage as the membrane fixed charge concentration increases. It is desirable to minimize the membrane co-ion concentration to achieve good salt rejection in reverse osmosis and good selective counter-co-ion transport of counterions through electrodialysis membranes. As the concentration of fixed charges in the membrane increases, the co-ion concentration in the membrane decreases. The Manning's parameter, which characterizes the dimensionless density of fixed charges, must be high to keep co-ion absorption and transport selectively low, and as the average distance between fixed charges on the membrane increases, the Manning's parameter decreases.The method for calculating Manning's parameter is disclosed in J. Kamcev, M. Galizia, FM Benedetti, E.-S. Jang, DR Paul, BD Freeman, and GS Manning, "Partitioning of Mobile Ions Between Ion Exchange Polymers and Aqueous Salt Solutions: Importance of Counter-ion Condensation," Physical Chemistry Chemical Physics, 18, 6021-6031 (2016), which is incorporated herein by reference. Thus, as the degree of disulfonation increases in these poly(arylene ether sulfone) membranes (i.e., the distance between the fixed charge groups decreases), the Manning's parameter increases and the absorption and transport of co-ions decreases. However, the Manning's parameter does not take into account the difference in the distribution of the fixed charge groups on the polymer backbone.

[0070] Description of Various Embodiments. Although sodium chloride rejection by disulfonated linear and crosslinked poly(arylene ether) membranes derived from pre-disulfonated sulfone monomers is good, when a mixed feed of salts containing monovalent and polyvalent cations is tested, the otherwise good sodium chloride rejection of some membranes is significantly impaired by the presence of the polyvalent cations. This is shown in FIG. 14, where the salt rejection of a linear disulfonated poly(arylene ether sulfone) with 20% of the repeat units disulfonated is tested against a feed water containing a mixture of sodium chloride and calcium chloride. This is a major obstacle to the usefulness of such membranes, since virtually all water to be desalinated contains significant amounts of polyvalent salts in addition to monovalent salts. The reasons for this undesirable behavior with a mixed feed of salts are not fully understood.

[0071] A series of sulfonated poly(arylene ether sulfones) with different chemical structures were prepared to identify membranes whose sodium chloride rejection was not significantly impaired by the presence of polyvalent salts mixed with monovalent salts. Monosulfonated hydroquinone-based linear polymers (postsulfonated) (SHQS-XX) (I) [ka] Monosulfonated biphenol-based linear polymers (presulfonated monomers) (mBPS-XX) (II) [ka] Disulfonated biphenol-based linear polymers (postsulfonated) (III). [ka] Disulfonated biphenol-based linear polymers (presulfonated monomers) (BPS-XX) (IV) [ka] Monosulfonated hydroquinone-based crosslinkable oligomers (postsulfonated) (V) [ka] Disulfonated biphenol-based crosslinkable oligomers (presulfonated monomers) (VI) [ka] These were compared to disulfonated biphenol-based membranes utilizing pre-disulfonated sulfone monomers (structure IV, previously BPS-XX), as illustrated in FIG. 14. These included high molecular weight linear copolymers with somewhat different backbone structures, copolymers in which the sulfonate anions are on adjacent rings on the sulfone units versus those in which the sulfonate anions are on adjacent rings on the biphenol units, copolymers in which two adjacent rings are not sulfonated, and sulfonated oligomeric copolymers that are subsequently crosslinked. Unexpectedly, key features of some of these structures were identified that alleviate the problem of reduced monovalent salt rejection in the presence of multivalent salts. Sodium chloride rejection results in a mixed sodium chloride / calcium chloride feed are shown in Table 2. Water permeability (Lμmm -2 time -1 bar -1 or cm 2 seconds -1 ), salt permeability (cm 2 seconds -1 ), salt rejection (%) and water / NaCl selectivity were measured at 25°C using a stainless steel cross-flow cell. 2 The pressure difference across the feed was 400 psi. The initial water feed contained 2000 ppm NaCl and the feed was 3.8 L min -1 The feed was circulated through the sample at a continuous flow rate of 1000 mg / L. The pH of the feed was adjusted to a range of 6.5–7.5 using 10 g / L sodium bicarbonate solution. The NaCl concentrations in the feed water and permeate were measured using an Oakton 100 digital conductivity meter. [Table 2] Table 2. Roman numerals in the entries refer to the structures shown above.

[0072] First, the only difference in the chemical structure of mBPS-XX copolymer (II) versus BPS-XX copolymer (IV) is that mBPS-XX (II) has sulfonate ions or isolated rings, whereas BPS-XX (IV) has sulfonate ions in two sets on adjacent sulfone rings. Both sets are random copolymers. The copolymers with sulfonate ions distributed along the chain in the two sets prepared from pre-disulfonated monomers (structure IV) take up significantly more water than the copolymers with sulfonate ions on isolated rings prepared from pre-monosulfonated monomers (structure II) (Table 3). [Table 3]

[0073] A comparison of mBPS-61 (II) and BPS-32 (IV), which have approximately equal numbers of ions (i.e., equal IEC), shows that the ring sulfonate-isolated copolymer (II) absorbs only about half the amount of water relative to the disulfonated BPS copolymer (IV). This makes the fixed charge concentration for mBPS-61 (II) significantly higher than that for BPS-32 (IV). This result is quite little loss in sodium chloride rejection with mBPS-61 in the presence of calcium salts, whereas it is significantly lost in BPS-32. The reason for the unexpected dramatic change in water absorption capacity with equivalent backbone structures and equivalent IEC remains unclear. Second, a comparison of entry 1 (SHQS-40 (I)) and entry 3 (mBPS-51 (II)) shows that these copolymers have equivalent water absorption with unequal numbers of ions (i.e., unequal IEC). This results in a higher fixed charge concentration for mBPS-51 than for SHQS-40 at equivalent amounts of water uptake and equivalent water permeability. Sodium chloride rejection in the presence of divalent calcium salts is good in both cases for the BPS copolymers, but is particularly outstanding for mBPS-51, which has a higher fixed charge concentration. In hindsight, the less polar backbone chemistry of mBPS-51 versus SHQS-40 may contribute to its ability to increase ion concentration but maintain lower water uptake. Sodium rejection versus the amount of calcium ions added to the sodium chloride feed is summarized in Figure 15. All of the copolymers in Figure 15, except for BPS-32, have sulfonates on isolated rings, whereas in BPS-20, the sulfonates are randomly distributed on adjacent rings, but in two sets. Thus, it is now recognized that sulfonated poly(arylene ether sulfone) membranes in which the sulfonate anions are randomly distributed along the chain on isolated rings rather than randomly distributed but in sets of two adjacent rings next to a sulfone moiety, have significantly improved monovalent salt rejection properties when exposed to salt-mixed feedwater.Surprisingly, the above structure I, in which the sulfonate ion is located on an adjacent ring on a biphenol unit (rather than on a sulfone unit), also does not show a significant reduction in monovalent salt rejection in the presence of CaCl. Thus, the actual placement of the sulfonate on the poly(arylene ether) is surprising with respect to its ability to possess high rejection of monovalent salts in mixed salt feedwaters that also contain multivalent salts.

[0074] Example 1. Synthesis of monosulfonated dichlorodiphenylsulfone monomer. 4,4'-Dichlorodiphenylsulfone (17.4 mmol, 5 g) was placed in a 250 mL round bottom flask equipped with a mechanical stirrer and a condenser and purged with nitrogen for 5 minutes. The nitrogen flow was stopped and oleum (19.1 mmol, 4.8 mL) was placed in the reaction flask. 4,4'-Dichlorodiphenylsulfone was dissolved in oleum at room temperature. Once dissolution was complete, the oil bath temperature was increased to 100°C. The reaction was allowed to proceed for 6-7 hours. After the reaction mixture was cooled to room temperature, the reaction flask was placed in an ice bath. Over a period of 10 minutes, a mixture of deionized water (40 mL) and ice (40 g) was slowly added to the reaction with stirring. After complete addition of the ice water, the reaction was heated to 65°C and NaCl (30 g) was slowly added to precipitate the mixture. The mixture was filtered and the filtrate was transferred back to the reaction flask. Deionized water (100 mL) was added to the flask to form a suspension containing both insoluble and soluble products. The suspension was neutralized by slow addition of 10 M aqueous NaOH. Neutralization was constantly checked with litmus paper. The suspension was reprecipitated by addition of NaCl (30 g) at 65° C. The precipitate was filtered and the solid filtrate was collected. The solid was dissolved in a mixture of deionized water (70 mL) and CHCl3 (30 mL) and the aqueous layer was collected. 1-butanol (150 mL) was added to the aqueous layer and the mixture was shaken and allowed to separate. The 1-butanol layer was collected, dried over MgSO4, and filtered. After evaporating the solvent via rotary evaporator, the product was recovered in 59% yield. The monosulfonated 4,4'-dichlorodiphenyl sulfone did not melt even when it reached the 300° C. limit of the melting point apparatus.

[0075] Synthesis of linear sulfonated poly(arylene ether sulfone)s by direct polymerization with isolated sulfonated rings. A series of monosulfonated biphenol-based poly(arylene ether sulfone)s (mBPS-XX) and disulfonated biphenol-based poly(arylene ether sulfone)s (BPS-XX) copolymers were synthesized using copolymerization of aromatic nucleophilic substitution steps. In this series, "XX" represents the degree of monosulfonation and disulfonation in mBPS and BPS, respectively.

[0076] Example 2. mBPS-80, in which 80% of the repeating units are monosulfonated, was synthesized as follows: Biphenol (14.96 mmol, 2.7863 g), 4,4-dichlorodiphenyl sulfone (2.2445 mmol, 0.6445 g), monosulfonated 4,4'-dichlorodiphenyl sulfone (12.85 mmol, 5.00 g), and DMAc (45 mL) were placed in a 250 mL round-bottom three-neck flask equipped with a mechanical stirrer, a condenser, a nitrogen inlet, and a Dean-Stark trap filled with toluene. The mixture was stirred in a 150° C. oil bath until the monomers were completely dissolved. K2CO3 (18.08 mmol, 2.5 g) and toluene (20 mL) were added to the flask. The reaction was refluxed for 4 hours to azeotropically remove water from the system. The toluene was drained from the Dean-Stark trap and the oil bath temperature was raised to 180° C. to remove residual toluene from the reaction. The reaction was stirred for 48 hours and then cooled to room temperature. The solution was diluted with DMAc (100 mL) and filtered to remove salts. The clear solution was precipitated by addition into isopropanol (1000 mL) with vigorous stirring. The white fibers were filtered and then stirred in boiling deionized water for 4 hours to remove any residual DMAc. The copolymer was filtered and dried in a vacuum oven at 120° C. under reduced pressure. 90% yield copolymer.

[0077] Example 3. Synthesis of linear sulfonated poly(arylene ether sulfone) containing sulfonated rings isolated by post-sulfonation. A series of hydroquinone-based poly(arylene ether sulfone) copolymers (HQSxx) were synthesized using aromatic nucleophilic substitution step copolymerization. HQS-60, in which 60% of the repeating units contain hydroquinone, was synthesized as follows. Hydroquinone (19.85 mmol, 2.186 g), 4,4'-dichlorodiphenyl sulfone (33.08 mmol, 9.501 g), bisphenol sulfone (13.235 mmol, 3.312 g), and sulfolane (43 mL) were placed in a 250 mL round-bottom three-neck flask equipped with a mechanical stirrer, a condenser, a nitrogen inlet, and a Dean-Stark trap filled with toluene. The mixture was stirred and heated in a 150° C. oil bath until the monomers were dissolved. K2CO3 (38.382 mmol, 5.305 g) and toluene (21 mL) were added to the flask. The reaction was refluxed for 6 h to azeotropically remove water from the system. The toluene was drained from the Dean-Stark trap and the oil bath temperature was raised to 200 °C to remove residual toluene from the reaction. The reaction was stirred at 200 °C for 47 h. The reaction mixture was filtered while hot to remove salts and precipitated in deionized water. The polymer was stirred in boiling deionized water for 4 h to remove any residual solvent. The polymer was filtered and dried in a vacuum oven at 120 °C under reduced pressure. For sulfonation, 10 g of the dried polymer was dissolved in 100 mL of concentrated sulfuric acid in a round-bottomed three-neck flask equipped with a nitrogen inlet and a thermometer, an overhead stirrer, and a condenser. An oil bath was used to maintain the temperature at 50 °C. The reaction was stirred vigorously to promote rapid dissolution. After maintaining the reaction temperature for 2 hours, the solution was precipitated into ice-cold water and rinsed thoroughly to remove residual acid. The polymer was stirred overnight in 1.0 M NaCl and dried at atmospheric pressure at 50° C. for 4 hours, followed by drying at 120° C. under vacuum for 12 hours.

[0078] Example 4. Oligomer synthesis using premonosulfonated monomer. The reaction scheme for the synthesis is shown in Figure 16. Molecular weight can be controlled by adjusting the stoichiometry of monomer and terminating reagents by well-known methods for step-extension polymerization. The following procedure is for a 10,000 g / mole oligomer terminated with crosslinkable tetrafluorostyrene end groups. 4,4'-Dichlorodiphenylsulfone (38.43 mmol, 11.04 g), monosulfonated 4,4'-dichlorodiphenylsulfone (38.43 mmol, 14.96 g), 4,4'-biphenol (80.55 mmol, 15.00 g), potassium carbonate (96.66 mmol, 13.35 g), dimethylacetamide (240 mL), and toluene (25 mL) were placed in a 500 mL round-bottom three-neck flask equipped with a mechanical stirrer, a Dean-Stark trap, a condenser, and a nitrogen inlet. The reaction vessel was immersed in an oil bath and heated to 150° C. to azeotropically dry the mixture for 4 hours. The toluene was drained from the Dean-Stark trap, and the oil bath temperature was increased to 180° C. for 48 hours. After allowing the reaction to cool to room temperature, pentafluorostyrene (72.44 mmol, 10 mL) was added to the reaction vessel and the mixture was heated to 110° C. for 2 hours. The reaction was diluted with dimethylacetamide (80 mL) and allowed to cool to room temperature. The reaction mixture was precipitated into stirring isopropyl alcohol (2500 mL), resulting in a white polymer. The polymer was filtered and added to stirring deionized water (3000 mL) at room temperature overnight to remove salts and residual DMAc. The polymer was isolated and dried under vacuum at 65° C. for 48 hours to give an 87% yield.

[0079] Example 5. Crosslinking of a thin film of the previously described oligomer at about 10,000 g / mol by free radical polymerization. The oligomer (0.4 g) was dissolved in 1 mL of dimethylacetamide. AIBN (0.008 g) was dissolved in this mixture. A clean glass plate was placed in an oven, continuously purged with nitrogen, and heated to 80° C. after lifting the plate. The polymer solution in DMAc was poured onto the plate and a scalpel with a gap of about 70 microns was used to spread the solution across the plate. After maintaining the temperature at 80° C. for 20 minutes, the film was immersed in deionized water to delaminate the film from the glass plate. The film was boiled in deionized water for 2 hours to remove residual dimethylacetamide, and then dried at 140° C. under vacuum for 24 hours. Thermogravimetric analysis showed that less than 2% dimethylacetamide / water remained. The film was submerged in dimethylacetamide at room temperature for 24 hours to extract the sol fraction. The mixture was vacuum filtered and the gel fraction was dried under vacuum at 140° C. for 24 hours. Thermogravimetric analysis showed that approximately 5% by weight of dimethylacetamide remained. The gel fraction was 85% by weight.

[0080] Another example was a mixture of 10,000 g / mole tetrafluorostyrene terminated oligomers and 2000 g / mole tetrafluorostyrene terminated oligomers. The oligomer mixture (0.7 g) contained 10,000 g / mole oligomers (0.585 g) and 2000 g / mole oligomers (0.115 g), and 17 mg of AIBN dissolved in 1.75 mL of dimethylacetamide. The mixture was cured at 80° C. under nitrogen for 20 minutes. The gel fraction after complete extraction with dimethylacetamide was 70%.

[0081] In another example, a mixture of 10,000 g / mole tetrafluorostyrene terminated oligomers and 2000 g / mole tetrafluorostyrene terminated oligomers was reacted with divinylbenzene as the low molecular weight reactant. The oligomer mixture (0.7 g) contained the 10,000 g / mole oligomer (0.585 g) and the 2000 g / mole oligomer (0.115 g). Divinylbenzene (7 mg) and 17 mg AIBN were dissolved in 1.75 mL dimethylacetamide. The mixture was cured at 80° C. under nitrogen for 20 minutes. The gel fraction after complete extraction with dimethylacetamide was 57%.

[0082] Alternatively, a tetrafluorostyrene functional oligomer of approximately 10,000 g / mol described previously was cured with light. The oligomer (0.4 g) and 4 mg of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) were dissolved in 0.9 mL of dimethylacetamide + 0.1 mL of diethylene glycol. The solution was placed on a glass plate and cured with 365 nm light at 60° C. for 3 seconds. The gel fraction of the film was 92% after complete extraction with dimethylacetamide.

[0083] Blends of oligomers of different molecular weights with functional end groups can be cured thermally or photocured by free radical polymerization. For example, a blend of a small amount of 2,000 g / mole tetrafluorostyrene terminated oligomer can be mixed with a large amount of 10,000 g / mole tetrafluorostyrene terminated oligomer and cured in a manner similar to that specified above in Example 5. Additionally, small amounts of low molecular weight monomers, such as about 1-5 weight percent divinylbenzene, may also be co-cured with such a mixture.

[0084] Controlled post-sulfonation of linear non-sulfonated poly(arylene ether sulfones), some of which contained hydroquinone comonomer and some of which contained biphenol, has also been achieved. The hydroquinone (or biphenol) ring in the copolymer must be the only ring activated for electrophilic aromatic sulfonation. By using mild sulfonation conditions, the activated ring can be quantitatively monosulfonated (for hydroquinone) or disulfonated (for biphenol) without sulfonating any of the other positions on the backbone.

[0085] The inventors have further discovered that terminally functionalized oligomers of controlled molecular weight can be prepared and then selectively post-sulfonated only at positions activated for electrophilic aromatic substitution. This aspect of the invention has an advantage over other membranes in that mono- or disulfonated monomers are not required. The method provides a means to prepare crosslinked sulfonated polysulfone networks without the need to synthesize preformed sulfonated monomers. By forming random copolymer oligomers by step-growth polymerization, the method allows for control of both the level of sulfonation and also the distribution of sulfonate anions along the oligomer backbone. These networks provide a means to improve fixed charge concentration without the need to synthesize and purify new monomers.

[0086] Historically, the post-sulfonation route resulted in an uncontrolled arrangement of sulfonic acid groups along the chain unless an otherwise special composition was utilized. Most previous studies on the post-sulfonation of polysulfones utilized rather harsh conditions since the rings to be sulfonated contained both activated and deactivated rings toward the electrophilic aromatic sulfonation reaction. For this reason, post-sulfonation as an approach to sulfonate poly(arylene sulfones) was abandoned due to the inability to control the degree of sulfonation, the microstructure of the sulfonated units, and the poor control over molecular weight loss due to chain scission during sulfonation. These post-sulfonated polysulfone membranes were found to be resistant to degradation by chlorine, but showed relatively low salt rejection relative to state-of-the-art interfacial polyamides. Alternatively, controlled post-sulfonation of poly(arylene ether sulfones) that contained hydroquinone or biphenol units can be performed. The sulfonation reaction could only proceed in hydroquinone (or biphenol) because all other rings were deactivated towards electrophilic aromatic sulfonation by the electron-withdrawing sulfone group. In this example, the reaction kinetics and measurement of the molecular weight of polysulfone containing hydroquinone were studied to optimize the sulfonation process by minimizing the level of chain scission. This information was used to develop a series of post-sulfonated polymers with varying architectures to determine structure-property relationships.

[0087] Description of Various Embodiments - Synthesis and Characterization of Controlled Molecular Weight Oligomers Produced by Post Sulfonation with Crosslinkable End Groups. A systematic series of oligomers with a range of hydroquinone contents were synthesized by varying the ratio of bisphenolsulfone and hydroquinone monomers. Polymerization is carried out via the carbonate method where K2CO3 deprotonates the phenol monomers to form an anionic nucleophile. The nucleophile attacks the negatively charged carbon attached to the halogen, releasing the halogen. A slight excess of K2CO3 is utilized to avoid any hydrolysis of the halogen-functional monomers, thus in turn preventing undesired end groups.

[0088] Reactions using post-sulfonation to produce aminophenol-terminated oligomers of controlled molecular weight by post-sulfonation: The first step is the synthesis of the non-sulfonated oligomer, the second step is post-sulfonation, and the third step is the regeneration of the amine end groups and the conversion of the pendant sulfonic acid groups to salts. In the second step, only the hydroquinone units are sulfonated, because all other rings are selected to be deactivated toward electrophilic aromatic sulfonation reactions, and therefore do not react under the mild conditions used in post-sulfonation. The sulfonation of hydroquinone is quantitative, so although an excess of sulfuric acid is used in the post-sulfonation reaction, controlling how much hydroquinone is loaded into the reaction allows control over the degree of sulfonation. Although Rose (U.S. Pat. No. 4,273,903, inventor for John B. Rose, Imperial Chemical Industries, Ltd, June 16, 1981) showed selective sulfonation of hydroquinone, he did not discuss any method to form oligomers of controlled molecular weight so that they could be functionalized with amine end groups or with other types of functional end groups. Therefore, Rose's patent does not disclose crosslinking reactions or crosslinked polymers. The copolymer portion derived from bisphenol sulfone does not undergo post-sulfonation, whereas the portion derived from hydroquinone does. There are other bisphenols (listed later) that could potentially be used with bisphenol sulfone as a replacement for hydroquinone. An example utilizing biphenols instead of hydroquinone is provided herein. During post-sulfonation, approximately one ion on each ring is sulfonated (the use of bisphenols is not included in Rose's 1981 patent). [ka]

[0089] The following structures show other bisphenols that are useful for post-sulfonation in addition to hydroquinone, where each R can independently be H or CH3. [ka]

[0090] Example 6. Synthesis of amine-terminated hydroquinone polysulfone oligomer for subsequent post-sulfonation and crosslinking. 10,000 g / mol M n Reactions for preparing amine-terminated oligomers of are provided. It is recognized that other molecular weights may be synthesized by adjusting the stoichiometry of the reactants. Hydroquinone (2.642 g, 24 mmol), bisphenol sulfone (6.006 g, 24 mmol), and m-aminophenol (0.436 g, 4 mmol) were dissolved in 67 mL of sulfolane in a round bottom three neck flask equipped with a nitrogen inlet, overhead stirrer, and condenser with a Dean Stark trap. Toluene (34 mL) and K2CO3 (8.624 g, 62 mmol) were added and the reaction was refluxed at 180-185 °C to azeotropically remove any water. After 4 hours, toluene was removed from the Dean Stark trap. 4,4'-dichlorodiphenyl sulfone (14.358 g, 50 mmol) was added to the reaction and the reaction temperature was increased to 200-210 °C. After 48 hours, the mixture was allowed to cool to approximately 150°C and then diluted with 40 mL of N,N-dimethylacetamide. The solution was filtered while hot to remove salts and then precipitated in isopropanol. The polymer was boiled in water with three changes of water to remove traces of sulfone, then dried at 50°C for 4 hours and then at 110°C under vacuum for 12 hours. The reaction had a 97% yield.

[0091] Example 7. Synthesis of amine-terminated biphenol polysulfone oligomer for subsequent post-sulfonation and crosslinking. 10,000 g / mol M n A reaction to prepare an amine-terminated oligomer of is provided. Bisphenol (4.34 g, 0.0233 mol), bisphenol sulfone (15 g, 0.06 mol), and m-aminophenol (0.828 g, 0.0076 mol) were dissolved in 123 mL of sulfolane in a round-bottomed, three-necked flask equipped with a nitrogen inlet, an overhead stirrer, and a condenser with a Dean Stark trap. The reaction temperature was controlled with a temperature controller connected to a thermocouple in a salt bath. Toluene (34 mL) and K2CO3 (13.80 g, 0.10 mol) were added and the reaction was refluxed at 180-185 °C to azeotropically remove any water. After approximately 4 h, the toluene was removed from the Dean Stark trap. 4,4'-Dichlorodiphenylsulfone (24.97 g, 0.087 mol) was added to the reaction flask and the reaction temperature was raised to 200-210 °C. After 48 hours, the mixture was allowed to cool to approximately 150 °C and then diluted with 30 mL of N,N-dimethylacetamide. The mixture was filtered while hot and maintained above the melting point of sulfolane (27.5 °C) while being precipitated in isopropanol to remove traces of solvent. The polymer was boiled in three changes of water to remove traces of sulfone and then dried at 50 °C for 4 hours and then at 110 °C under vacuum for 12 hours.

[0092] Example 8. Postsulfonation of amine-terminated hydroquinone polysulfone oligomer. Dry 10,000 g / mol M n The hydroquinone polysulfone oligomer (10 g) was dissolved in 100 mL of concentrated sulfuric acid in a round-bottomed three-neck flask equipped with a nitrogen inlet and a thermometer, an overhead stirrer, and a condenser. An oil bath was used to maintain the reaction temperature at 50° C. After 2 hours of reaction, the solution was precipitated into ice-cold water, followed by rinsing with water to remove excess acid until litmus paper showed no traces of acid in the filtrate. The sulfonated polysulfone oligomer with ammonium end groups was converted to the salt form, and the ammonium end groups were converted to amines by stirring with 0.1 M aqueous NaOH for 6 hours. The amine-terminated sulfonated hydroquinone polysulfone oligomer was filtered and dried at 50° C. at atmospheric pressure for 7 hours, then at 110° C. under vacuum for 12 hours. Proton NMR showed that the hydroquinone units had been sulfonated. A water-insoluble product was obtained, and no decomposition of the oligomer was observed. The mild reaction conditions only resulted in the substitution of a sulfonic acid group on the activated hydroquinone for electrophilic aromatic sulfonation.

[0093] FIG. 17 shows the structure of the 10k-65-HQS oligomer, which shows quantitative terminal end group functionality. 1 The H NMR spectrum is provided. The fraction of hydroquinone-containing units is 1 The H NMR spectrum was confirmed (FIG. 17). The integral corresponding to the amine peak (I) was normalized by 4, and the integral of the cluster of peaks from the protons close to the sulfone group was subtracted from the integral of the cluster of peaks B, B1, and C to obtain the number of protons on the hydroquinone unit. Hence, the molecular weight of the oligomer was calculated by determining the number of hydroquinone units per bisphenol sulfone unit.

[0094] Figure 18 shows the 10k-65-SHQS 1 1 H NMR is provided. Quantitative monosulfonation of the hydroquinone ring in the oligomer is shown in FIG. 1 This was confirmed by H NMR. A broad peak was observed due to the presence of water and hydrophilic properties. However, the appearance of peak C' was observed simultaneously with the disappearance or reduction in the C peak. 1 H NMR spectroscopy (Figure 19) confirmed that the C' peak corresponds to the proton next to the sulfonic acid group, since it did not correlate with any other protons. Figure 19 provides the COSY NMR data for 10k-65-SHQS, which confirms sulfonation only on the hydroquinone unit.

[0095] End group analysis of oligomers by fluorine derivatization. Amine-terminated oligomers containing amine end groups, and any residual phenol end groups, were reacted with trifluoroacetic anhydride to produce the respective trifluoroacetic acid derivatives. The reaction is provided for the derivatization of 5,000 g / mol of an amine-terminated oligomer in which 50 mol % of the bisphenol moieties are hydroquinones (50-HQS-5k). The 50-HQS-5k oligomer (200 mg, 0.040 mmol) along with the amine end groups and possibly unreacted hydroxyl end groups was dissolved in 5 mL of CHCl3 in a 25 mL flask and trifluoroacetic anhydride (0.5 mL, 3.53 mmol) was added. The reaction mixture was kept at 25° C. for 12 hours. Deionized water (100 mL) was added to the reaction mixture to hydrolyze the residual anhydrides, and the mixture was stirred at room temperature for 2 hours. The organic phase was separated and the amine-terminated oligomer was dissolved in 5 mL of CHCl3 in a 25 mL flask along with the amine end groups and possibly unreacted hydroxyl end groups. 19 The product was analyzed by F NMR.

[0096] Figure 25 provides an overview of the synthesis of random oligomers of controlled molecular weight by electrophilic aromatic substitution. x=0.40, 0.50, 0.65, 0.80. Figure 27 provides an overview of fluorine derivatization of oligomers to check for unreacted monomer and reaction completion.

[0097] To confirm the absence of unwanted residual phenol or chlorine end groups after the reaction, the oligomers were derivatized with trifluoroacetic anhydride, as shown in Figure 27. The anhydride reacts with the amine end groups to give 19 It forms a derivative that resonates at a maximum at about 74 ppm in the F NMR spectrum (Figures 28A and 28B). The anhydride also reacts with any unreacted end groups of the Bis-S or hydroquinone, resonating with the product from the amine. An aliquot taken at 24 hours showed that there was one equivalent of phenol from Bis-S for just five equivalents of amine. However, an aliquot taken at 36 hours showed that the reaction had gone to completion successfully. Figure 28A shows the structure of the oligomer aliquot showing the unreacted hydroxyl end groups and amine groups of the oligomer aliquot at 24 hours into the reaction. 19 FIG. 28B provides the F NMR spectrum of only the amine end groups of an aliquot of the oligomer at 36 hours of reaction. 19 F NMR spectrum is provided.

[0098] Figure 20 provides the light scattering SEC curves of 10k-65-SHQS and 10k-65-HQS to confirm the molecular weight. Figure 20 shows the symmetric light scattering curves. The elution time of the sulfonated oligomers was shorter than that of the non-sulfonated counterparts (Figure 20). The molecular weights and percentages of hydroquinone units are shown in Table 4. [Table 4] Table 4. Molecular weight summary.

[0099] Example 9. Postsulfonation of amine-terminated biphenol polysulfone oligomers Postsulfonation of the amine-terminated biphenol polysulfone oligomers was carried out in the same manner as the amine-terminated hydroquinone polysulfone oligomers described in Example 8. One sulfonate on each biphenol ring resulted.

[0100] Example 10. Crosslinking of amine-terminated post-sulfonated hydroquinone polysulfone oligomers with epoxy reagents. Thin film casting involved crosslinking of post-sulfonated telechelic oligomers with the crosslinker TGBAM using triphenylphosphine as a catalyst. The crosslinking reaction was carried out above the Tg of the oligomer, which was inhibited by the solvent (DMAc). The IEC of the crosslinked networks was lower than the precursor oligomer due to the incorporation of the hydrophobic TGBAM. The fixed charge concentration was calculated as the ratio of the IEC to the incorporation of water. High gel fractions (approximately 90%) were observed for all of the networks. [ka]

[0101] Provides crosslinking reaction for 10,000 g / mol oligomer. n of amine-terminated post-sulfonated hydroquinone polysulfone oligomer (0.046 mmol, 0.63 g), tetraglycidylbis(p-aminophenyl)methane (0.114 mmol, 0.048 g) and triphenylphosphine (5.5 × 10 -3 1.2 mmol, 1.44 mg) was dissolved in 8 mL of N,N-dimethylacetamide. The solution was syringe filtered through a 0.45 μm polytetrafluoroethylene filter. The solution was poured into a circular Teflon mold with flat edges and a diameter of 10 cm. The mold was placed on a raised surface in a 70° C. oven. The temperature was ramped from 70° C. to 175° C. over 6 hours and the film was cured at 175° C. for 12 hours. The epoxy-cured network was removed from the Teflon mold by immersion in deionized water and dried.

[0102] A summary of the IEC, water uptake and gel fraction is provided in Table 5. The crosslinked films were dried overnight under vacuum at 120 °C. After drying, 0.1-0.2 g of sample was placed in a 20 mL scintillation vial filled with DMAc and stirred at 100 °C for up to 12 h. The remaining solids were filtered, transferred to a weighing vial and dried at 160 °C under vacuum for up to 12 h before being weighed. For each film, triplicate measurements were performed and the gel fraction was calculated by Equation 1.

number

number

[0103] Hydrated tensile properties. Water absorption pulls the polymer network, and this pull is resisted by elastic traction forces. Hence, the tensile properties of the network depend on water uptake. Upon increase in water uptake, the strength and modulus dropped, but the hydrated network remained in a glassy state. Figure 21A provides a graph of modulus versus water uptake for a fully hydrated membrane. Figure 21B provides a plot of strength versus water uptake for a fully hydrated membrane. Figure 21C provides a schematic of crosslinking of post-sulfonated amine-terminated oligomers.

[0104] Networks prepared with about 5,000 g / mole oligomers and about 10,000 g / mole oligomers show different trends in terms of the ultimate strain at the fully hydrated state of the network. Figure 22A provides the stress-strain curves of the fully hydrated membranes of the 5k-XX-SHQS series, and Figure 22B provides the stress-strain curves of the fully hydrated membranes of the 10k-XX-SHQS series. The 5000 g / mole series networks were constrained to an ultimate strain of about 5.5%. This may be due to the hydrostatic forces becoming much greater than the elastic forces of the polymer network as the network absorbs more water. The 10,000 g / mole oligomer network has a higher water uptake than its 5000 g / mole counterpart, which may be partially due to the smaller amount of hydrophobic cross-linking reagent used to cross-link the 10,000 g / mole oligomer. The crosslinker not only reduced the hydrophilicity of the system due to its inherent hydrophobicity, but also reduced the flexibility of the 5000 g / mol network to a greater extent than the network prepared with the 10,000 g / mol oligomer, which made the network made with the 5000 g / mol oligomer more brittle than the network containing the 10,000 g / mol prepolymer. Hence, the network containing the 10,000 g / mol prepolymer was more flexible due to the longer chain length between crosslinks.

[0105] Example 11. Reaction of amine-terminated post-sulfonated polysulfone oligomers with end groups for subsequent free radical crosslinking, then crosslinking the oligomer with light. Amine-terminated post-sulfonated polysulfone oligomers can be reacted with acrylate and methacrylate reagents to produce acrylate, methacrylate, acrylamide or methacrylamide end groups. These functional oligomers can then be crosslinked by free radical polymerization, thermally or with light. It is recognized that alternative functional end groups and / or alternative crosslinking reagents can be used in a similar manner to produce crosslinked membranes, where controlled molecular weight oligomers or blends of different molecular weight oligomers are utilized as macromonomers. Examples of alternative functional end groups are phenol, maleimide, nadimide, acrylate, methacrylate, acrylamide, methacrylamide, ethynyl, phenylethynyl, styrene, tetrafluorostyrene and others. Alternative cross-linking reagents are amine, azide, benzylic halide type monomers, and comonomers including molecules with double bonds reactive by free radical polymerization. [ka]

[0106] Functionalization of amine-terminated post-sulfonated hydroquinone polysulfone oligomers with acryloyl chloride to produce post-sulfonated oligomers that are crosslinkable by free radical polymerization. [ka]

[0107] Approximately 10,000 g / mol M n A procedure is provided for the synthesis of an amine-terminated, post-sulfonated hydroquinone polysulfone oligomer with 40% of the repeating units sulfonated. The oligomer (2 g, 2×10 -4 The mixture was azeotroped in an oil bath set at 160° C. to remove any water for 4 hours. It was cooled to 0° C. in an ice bath, and then anhydrous triethylamine (1.53 mL, 11×10 -3 mol) was added, followed by acryloyl chloride (0.36 mL, 4.4 × 10 -3 (mol) was added by syringe. Stirred at 0°C for 3 h, then precipitated in isopropanol, washed with isopropanol for 12 h, filtered, dried at 80°C under vacuum for 24 h, then stored in the dark in a refrigerator. Proton NMR showed quantitative appearance of acrylamide end groups. Oligomer (0.4 g) and 1 mg of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) were dissolved in 0.5 mL of dimethylacetamide + 0.5 mL of diethylene glycol. The solution was placed on a glass plate and cured at 60°C for 5 min with 385 nm light. The gel fraction of the cast film was 92% after complete extraction with dimethylacetamide.

[0108] Example 12. Postsulfonation of phenol-terminated oligomers and then functionalization of the end groups for free radical polymerization. Postsulfonated oligomers can also be prepared with phenol end groups by offsetting the stoichiometry by known methods to control molecular weight, and then further functionalized so that they can be crosslinked by free radical polymerization using either heat or light with an initiator. This procedure involves synthesizing an oligomer containing bisphenol sulfone with a bisphenol that can be selectively sulfonated under mild conditions, postsulfonating the oligomer, and then reacting the phenol-terminated sulfonated oligomer with pentafluorostyrene, acryloyl chloride, or isocyanatoethyl acrylate, methacryloyl chloride, or isocyanatoethyl methacrylate to form crosslinkable end groups. These can be further reacted in the presence of either heat or ultraviolet initiator with light to produce crosslinked networks. Networks with tetrafluorostyrene end groups would be expected to be particularly chlorine stable.

[0109] Salt permeability. The salt permeability of the polymer networks was measured under a concentration gradient where the upstream salt concentration was kept constant for all measurements. The salt permeability is plotted against the water uptake and fixed charge concentration (Figures 23 and 24). It was observed that with the decrease in the water content in the network, the salt permeability decreased for all the networks (Figure 23). However, this trend was due to the block length of the prepolymer. The 5,000 g / mol oligomers contain an average of just about 10 repeat units, which is above the entanglement length threshold, which may make both the hydrated mechanical properties of the oligomers and the transport properties of the oligomers more sensitive to even small changes in water uptake or fixed charge concentration. However, the 10,000 g / mol block appears to be more entangled, which may explain why the mechanical properties and transport control of the block are less sensitive to changes in water uptake or fixed charge concentration than the 5000 g / mol oligomer network.

[0110] The observed trends in salt permeability versus fixed charge concentration can be explained based on Donnan equilibrium. The higher the fixed charge concentration, the greater the concentration of co-ions (i.e., Cl) in these membranes. - ) rejection is greater and salt permeability is lower. Hence, it was observed that the salt permeability dropped sharply with increasing fixed charge concentration (Figure 24).

[0111] Electrodialysis (ED) requires high counterion vs. co-ion selectivity and high permeability of counterions. Counterion permeability increases with increasing water content since water provides the flow medium for the ions. However, this increased water uptake reduces the fixed charge concentration, especially for linear ion exchange polymer membranes, so water uptake must be optimized. Low co-ion permeability, which manifests itself as low salt permeability, is not only necessary in ED, but also in other desalination processes such as RO and forward osmosis, which utilize ion exchange membranes and where high salt rejection is desired. To optimize water uptake and fixed charge concentration, the membranes of the present invention were crosslinked. The salt permeability was somewhat mitigated by crosslinking. 10k-65-SHQS exhibits these optimal properties not only in terms of water uptake and salt permeability, but also in hydrated mechanical properties. 10k-65-SHQS exhibited a hydration coefficient of about 700 mPa. The cured membranes absorbed large amounts of water as the degree of sulfonation increased, but remained in a glassy state even when fully hydrated. The yield strength of the fully hydrated, cross-linked networks was in the range of approximately 10–25 MPa.

[0112] Structure and molecular weight of functional oligomers. Non-sulfonated and sulfonated oligomers are quantitatively characterized to calculate the molecular weight and degree of sulfonation. 1 H NMR was characterized (Figures 17 and 18). The completion of the reaction was confirmed by the absence of unwanted end group peaks in the spectrum. The peak from the amine end group was used to normalize the spectrum.

[0113] The A, A1 signals overlapped and resonated from 7.88 to 8.02 ppm. The I peak from the amine end groups resonated at 5.33 ppm. The C protons of hydroquinone resonated at 7.2 ppm. After sulfonation, the C protons shifted to 7.45 ppm due to the electron-withdrawing nature of the deprotonated sulfonic acid group. The amine end groups were acidified during sulfonation at 50° C. for 2 hours, shifting the peak downward. Thus, the sulfonated oligomer was stirred in 0.1 N NaOH solution to recover the amine end groups. Figures 17 and 18 show the structure of an oligomer with a target molecular weight of about 5000 g / mol and 65% hydroquinone-containing repeat units before (Figure 17) and after (Figure 18) sulfonation. 1 H NMR is provided.

[0114] The sulfonation degree was calculated from the spectrum of the sulfonated oligomer, and the ion exchange capacity was calculated using the sulfonation degree (Equation 3). In Equation 3, DS is the sulfonation degree, MW SRU Na + is the molecular weight of the sulfonated repeating unit in the form NSRU is the molecular weight of the non-sulfonated repeat unit.

number

[0115] A COSY NMR experiment was performed to confirm the structure of the post-sulfonated oligomer (FIG. 19). The C' proton was only correlated with itself and did not show any three-body bond correlation with any other protons. There were no other uncorrelated protons. Thus, there were no secondary sites of sulfonation and all of the hydroquinone moieties were strategically sulfonated by post-sulfonation. FIG. 19 provides the COSY-NMR of the sulfonated oligomer with a target molecular weight of about 5000 g / mol and a repeat unit containing 65% hydroquinone (65-SHQS-5k).

[0116] Membrane properties. The maximum water absorption increases with IEC (Figure 33, Table 8). Figure 33 provides plots showing the fixed charge concentration of linear and crosslinked (-5000 g / mol) membranes as a function of the ion exchange capacity of these membranes. The IEC of the crosslinked membranes was 1 The IEC of the oligomers measured by H NMR was calculated by taking into account the addition of a non-ionic crosslinker (Equation 4). It has been reported that the water uptake of crosslinked membranes is constrained by reduced swelling and free volume. This is evident for the systems considered in this example in Figure 32, where for a given IEC, the water uptake of the epoxy network prepared from the 5000 g / mol oligomer is less than that of its linear counterpart.

number

[0117] [Table 6]

number

[0118] Mechanical properties of hydrated membranes. One of the objectives of this example is to develop membranes with superior mechanical properties under fully hydrated conditions to withstand high applied pressures in reverse osmosis. Linear and crosslinked SHQS membranes are glassy under fully hydrated conditions. Figure 35 provides plots showing the decrease in yield strength and elastic modulus with increasing water uptake for crosslinked and linear SHQS membranes. Tensile data (Figure 35) showed that increasing water uptake decreased the elastic modulus and yield strength in the crosslinked network. This phenomenon occurred due to the plasticizing effect of water, independent of the degree of crosslinking. The high dielectric constant of water reduces the van der Waals forces between the polymer chains, leading to an increase in free volume and chain mobility. Interestingly, a similar trend was observed in the linear samples as shown in Figure 35. It can therefore be concluded that the effect of water content supersedes the effect of block length and crosslinking on the hydrated mechanical properties. This was because the crosslinked membranes were designed with controlled crosslinking only at both ends and had low crosslink density. The 50SHQS-5k network showed the highest strength with the least amount of water uptake (0.14).

[0119] INCORPORATION BY REFERENCE AND VARIATIONS STATEMENT All references throughout this disclosure, for example, issued or accepted patents or equivalents, patent documents including published patent applications, and non-patent literature or other source materials, are hereby incorporated by reference in their entirety as if each were individually incorporated by reference in its entirety. Specific documents hereby incorporated by reference include U.S. Patent No. 8,028,842 and U.S. Patent No. 4,273,903.

[0120] All patents and publications mentioned in this disclosure are indicative of the level of skill of those skilled in the art to which this invention pertains. References cited in this specification, in some cases as of the filing date, are incorporated herein by reference in their entirety to indicate the state of the art, and it is contemplated that this information can be adopted herein and, if necessary, specific embodiments existing in the prior art can be excluded (e.g., abandoned). For example, when a compound is claimed, it should be understood that compounds known in the prior art are not contemplated to be included in the claims, including certain compounds disclosed in the references disclosed herein (e.g., in the patent documents referenced).

[0121] When a group of substituents is disclosed herein, it is understood that all individual members of the group, as well as all subgroups and classes that can be formed using the substituents, are disclosed separately. When a Markush group or other grouping is used herein, all individual members of the group and all possible combinations and subcombinations of the group are intended to be individually included in the disclosure. As used herein, "and / or" means that one, all, or any combination of the items in the list separated by "and / or" is included in the list, for example, "1, 2, and / or 3" is equivalent to "'1' or '2' or '3' or '1 and 2' or '1 and 3' or '2 and 3' or '1, 2, and 3'."

[0122] Any formula or combination of components described can be used to practice the invention unless otherwise stated. Specific names of materials are intended to be exemplary when those skilled in the art know that the same materials can be called by other names. It will be recognized that methods, device elements, starting materials, and synthetic methods other than those specifically exemplified can be employed in the practice of the invention without relying on undue experimentation. All art-known functional equivalents of any such methods, device elements, starting materials, and synthetic methods are intended to be included in the present invention. Whenever a range is given in the specification, such as a temperature range, time range, or composition range, all intermediate ranges and subranges are intended to be included in the disclosure, as well as all individual values ​​included in the given range. It will be recognized that the chemical structures shown herein illustrate specific exemplary diagrams for a particular molecule, and that other equivalent diagrams may exist for the same molecule.

[0123] As used herein, "comprising" is synonymous with "including," "containing," or "characterized by," and is inclusive or open ended, and does not exclude additional, unrecited elements or method steps. As used herein, "consisting of" does not exclude any element, step, or ingredient not embodied in the claimed element. As used herein, "consisting essentially of" does not exclude materials or steps that do not materially affect the basic and novel characteristics of the claim. Any recitation herein of the term "comprising," particularly in the description of a component of a composition or in the description of an element of a device, is to be understood to include compositions and methods consisting essentially of and consisting of the recited components or elements. The invention as suitably illustrated herein can be practiced in the absence of any element or elements, limitation or limitations not specifically disclosed herein.

[0124] The terms and expressions which have been employed are used as terms of description and not of limitation, and there is no intention to use such terms and expressions to exclude any equivalents of the features or portions thereof shown and described, but it is recognized that various modifications are possible within the scope of the invention claimed. Thus, although the present invention has been specifically disclosed by preferred embodiments and optional features, it must be understood that modifications and variations of the concepts disclosed herein may be resorted to by those skilled in the art, and such modifications and variations are deemed to be within the scope of the invention, as defined by the appended claims.< / ps>

Claims

1. The structure: 【Chemistry 1】 A random copolymer for a water desalination membrane, wherein each L 1 is independent 【Chemistry 2】 and each L 2 is independent 【Chemistry 3】 and each L 3 are independently single bonds, 【Chemistry 4】 and one Y 1 SO 3 Z and another Y 1 is H, Z is a counterion, and each R is independently H, F, or CH 3 and the value of x is between 0 and 1, but not 0 or 1, and the value of n is between 2 and 100,000.

2. It further comprises one or more terminal groups A, each terminal group A being H, 【Chemistry 5】 Phenol, aromatic amines derived from aminophenols as end-capping agents in copolymerizations, or 【Chemistry 6】 Independently selected from, X is a halogen, and one Y 1 SO 3 Z and another Y 1 is H, or both Y 1 The random copolymer according to claim 1 , wherein

3. It further comprises one or more end groups A, each end group A being 【Chemistry 7】 The random copolymer according to claim 1 , wherein the random copolymer is independently selected from:

4. A crosslinked network comprising the random copolymer of claim 2 or claim 3 in crosslinked form, a blend of different molecular weights of the random copolymers of claim 2 or claim 3 in crosslinked form, or a single molecular weight or a blend of different molecular weights of the random copolymers of claim 2 or claim 3, in crosslinked form, and one or more small molecule polymerizable reagents.

5. The structure: 【Chemistry 8】 A random copolymer for use in a desalination membrane of the present invention, wherein each L 1 Independent 【Chemistry 9】 Each L 2 but 【Chemistry 10】 and each L 3 are independently a single bond, 【Chemistry 11】 and at least one or both of Y 1 SO 3 Z, Z is a counterion, and each R is independently H, F, or CH 3 and the value of x is between 0 and 1, but not 0 or 1, and the value of n is between 2 and 100,000.

6. Each L 2 but 【Chemistry 12】 And L 3 is a single bond, and at least one or both of Y 1 SO 3 Z, Z is a counterion, and each R is H or CH 3 The random copolymer according to claim 5 ,

7. The structure: 【Chemistry 13】 A random copolymer of the formula: 1 Independent 【Chemistry 14】 and each L 2 Independent 【Chemistry 15】 and each L 3 are independently a single bond, 【Chemistry 16】 and at least one or all of Y 1 SO 3 Z, Z is a counterion, and each R is independently H, F, or CH 3 and further comprising one or more end groups A, each end group A being an aminophenol, 【Chemistry 17】 and the value of x is between 0 and 1, but is not 0 or 1, and the value of n is from 2 to 100,000.

8. The random copolymer according to claim 7 in crosslinked form; A crosslinked network comprising a blend of different molecular weights of the random copolymers of claim 7 in crosslinked form, or a single molecular weight or a blend of different molecular weights of the random copolymers of claim 7 in crosslinked form and one or more small molecule polymerizable reagents.

9. A water desalination membrane comprising the random copolymer according to any one of claims 1 to 3 or 5 to 7.

10. 10. The water desalination membrane of claim 9, exhibiting greater than 95% rejection of water soluble monovalent ions in the presence of multivalent cations.

11. A water desalination membrane comprising the crosslinked network of claim 4.

12. 12. The water desalination membrane of claim 11, exhibiting greater than 95% rejection of water soluble monovalent ions in the presence of multivalent cations.

13. A water desalination membrane comprising the crosslinked network of claim 8.

14. 14. The water desalination membrane of claim 13, exhibiting greater than 95% rejection of water soluble monovalent ions in the presence of multivalent cations.

15. 10. The water desalination membrane of claim 9, wherein a first side of the water desalination membrane is exposed to a saltwater solution, the saltwater solution comprises a mixture of monovalent and multivalent cations, the saltwater solution comprises a chlorine-based sterilant, and the water desalination membrane remains substantially unoxidized by the chlorine-based sterilant.

Citation Information

Patent Citations

  • Sulfonated polyaryletherketone

    JP1980036296A

  • Sulfonated polyaryl ether ketone copolymer and manufacturing process

    JP1982025328A

  • Chlorosulfonated polysulfone and derivatives

    JP1984196321A

  • Polyelectrolyte film and its preparation

    JP1994093114A

  • Ion conductive binding agent for fuel cell, composition and varnish for forming electrode, and fuel cell

    JP2004047244A